Pembinaan Kelas Ibu Hamil Untuk Meningkatkan Pengetahuan Kesehatan Reproduksi Di Puskesmas Deli Tua Tahun 2025 - Tifani Hadi Tri Wahyuni (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Maternal reproductive health is a critical factor in reducing Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). Data from Deli Tua Primary Health Center shows that K4 coverage reached only 78% with prenatal class participation at 40%, still below the national target. Low knowledge among pregnant women about reproductive health is one of the main causes. This Community Service Student Creativity Program (PKM-M) aims to improve reproductive health knowledge through innovative and interactive prenatal class improvement. The implementation method includes developing educational media (modules, posters, videos), conducting classes with participatory learning methods, and evaluation through pre-post tests. The program was conducted over 5 months targeting 30 pregnant women divided into 3 groups, each attending 6 sessions. Materials covered physiological changes during pregnancy, nutrition, reproductive hygiene, danger signs, childbirth preparation, and postpartum care. Results showed a knowledge score increase of 42.5% (from 58.3±12.4 to 83.1±8.7) with significance p<0.001. Participation reached 86.7% with satisfaction level of 4.3/5.0. The program proved effective in improving reproductive health knowledge and can be replicated in other primary health centers with local context adaptation.